Technology and the dis-placing of learning in educational futures - Crook, Charles; Bligh, Brett (Elsevier, 2016)
Common visions of online education entail radically re-configuring the experience of learning: a technological displacement from the spatial order of classrooms into the more diffuse arena of digital networks. One assumption seems to be that the very spatial order of classrooms creates an undesirably rigid sense of place for schooling, one that is depressingly impervious to change; and that the attendant solution is to escape the realm of the ‘physical’ altogether – into an online realm more supportive of collaboration and free of face-the-front conventions. In the present paper we seek to challenge this oppositional view. We consider several ways in which digital technology can restructure the traditional spaces of educational practice, and identify design dynamics that may be neglected in the wake of ‘virtualisation’. Discussion first highlights two theoretical perspectives that will inform many such designs: namely, situativity and sociality in learning. Three examples are then provided of how digital technology can intersect with learning space design to create novel interpersonal frameworks for learning and to destabilise conventional senses of ‘place’ in those settings. The examples concern, respectively, the organisation of collaborative, expository, and community-based social structures for learning. Those examples represent an illustrative counterpoint to models of online schooling and illustrate a potentially productive synergy between the opportunities afforded by digital technologies, the desires of those who wish to dis-place learning online, and a well-established interest in learning space design.